Kualitas Pendidikan dan Keunggulan Kompetitif - Makmur Syukri; Nurul Farhaini (Journal on Education, 2024)
Education is an investment process that forms human resources who have the skills and skills to meet future demands. Achieving the goals of Education, it is necessary to have education with a quality education system. Education can be categorized as quality if it meets and can exceed the 8 educational standards listed in PP no. 19 of 2005. The quality of education has a positive impact as a form of competitive advantage that can be used as an aspect of competitiveness with other educational institutions. This article aims to describe specifically about the quality of Education and competitive advantage as competitiveness with other Educational Institutions. This article uses library research methods in its writing, by collecting data sourced from published scientific references. The results of this article found that the quality of education is illustrated if it meets 8 national education standards and can provide satisfaction to the needs of education stakeholders. The quality of education is also one of the materials of competitive advantage as the competitiveness of educational institutions. Generating competitive advantage requires strategy and analysis of strengths, opportunities of Educational Institutions such as through SWOT analysis.